Possibilities of Detecting an Epidemic Focus of Tuberculosis Infection in an Indicator Patient with a Positive Immunological Test for Tuberculosis - G. S. Oganezova; E. M. Bogorodskaya; N. I. Briko; E. M. Belilovsky (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. In connection with the advent of new diagnostic immunological tests, it became possible to determine a potential focus of infection not only through the identification of patients with tuberculosis, but also through the identification of patients infected with M. tuberculosis, who still do not have manifestations of a local form of the disease. This made it possible to search for persons who were infected with an unknown source of tuberculosis infection in order to conduct an in-depth epidemiological investigation and detect hitherto unknown foci of tuberculosis. Aims. To study the effectiveness of identifying the source of infection in the environment of a patient with a positive immunological test for tuberculosis («indicator» patient). Materials and methods. 1) A retrospective study of the data of all 30 patients with tuberculosis in the period from 2014 to 2019 in Moscow, identified by indicator patients with a positive immunological test, was carried out. 2) A cohort of patients with latent tuberculosis infection with and without HIV infection (Moscow) was studied in the period 2020–2021. to determine the prevalence of latent infection in the close circle of communication of indicator patients. Results. Patients with tuberculosis, forming hidden foci and identified by the indicator patients infected by them with a latent infection, in 56.7% of cases were not examined for tuberculosis for 2–10 years, in 50.0% they suffer from tuberculosis with registered bacterial excretion, in 46.7% of cases are internal or external migrants. The prevalence of latent tuberculosis infection among indicator patients is 10%, which is many times higher than the prevalence of latent tuberculosis infection among the permanent population of Moscow (less than 1%), in HIV-infected risk groups (up to 5%), in known foci of tuberculosis on average in Moscow (5%). The TB notification rate in the environment of indicator patients with latent tuberculosis infection is 38.8 per 100,000 of the corresponding group and exceeds that among the permanent population of Moscow by 5.4 times. Conclusion. A modified epidemiological investigation aimed at examining the environment of persons with latent TB infection among adults makes it possible to identify TB patients who have infected indicator patients and to identify other infected patients.